Formação continuada? : a aprendizagem de diretores escolares do Município de Vitória-ES - Módolo, Vinícius Medina (2018)
The aim of this paper is to analyze the impacts of the continuing education policy in the Municipal Education Department of Vitória on managerial learning from the school principals point of view, who were involved in this process. Beside a theoretical su